2013
DOI: 10.1007/s00198-013-2591-3
|View full text |Cite
|
Sign up to set email alerts
|

Locally measured microstructural parameters are better associated with vertebral strength than whole bone density

Abstract: Locally measured microstructural parameters are better associated with vertebral strength than whole bone densityHazrati Marangalou, J.; Eckstein, F.; Kuhn, V.; Ito, K.; Cataldi, M.; Taddei, F.; van Rietbergen, B. Published in: Osteoporosis International DOI:10.1007/s00198-013-2591-3Published: 01/01/2014 Document VersionAccepted manuscript including changes made at the peer-review stage Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Meshing was done using secondorder tetrahedron elements with a typical size of 2 mm; the number of elements on the proximal femur models varied from approximately 80,000 to 90,000 depending on the scan length. For all elements at the cortical/cancellous region, we calculated a bone volume fraction (BV/TV) and fabric tensor M as described earlier (Hazrati Marangalou et al 2014a. In summary, for the elements that were at least partly within the cancellous bone, a spherical region around the element centroid with a diameter of 4 mm was defined (Harrigan et al 1988) and the mean intercept length (MIL)-based fabric tensor was calculated for that spherical volume of interest using the image processing software provided by micro-CT system.…”
Section: Methodsmentioning
confidence: 99%
“…Meshing was done using secondorder tetrahedron elements with a typical size of 2 mm; the number of elements on the proximal femur models varied from approximately 80,000 to 90,000 depending on the scan length. For all elements at the cortical/cancellous region, we calculated a bone volume fraction (BV/TV) and fabric tensor M as described earlier (Hazrati Marangalou et al 2014a. In summary, for the elements that were at least partly within the cancellous bone, a spherical region around the element centroid with a diameter of 4 mm was defined (Harrigan et al 1988) and the mean intercept length (MIL)-based fabric tensor was calculated for that spherical volume of interest using the image processing software provided by micro-CT system.…”
Section: Methodsmentioning
confidence: 99%
“…First, these results mean that the trabecular component is definitely the primary factor to explain vertebral strength. Previous studies have proven that vertebral strength is mainly dependent on trabecular bone [14,[31][32][33]. Lu et al conducted mechanical compression tests of T12 vertebrae in elderly women (N = 20, average age: 80 years), and they reported that the factor that was most correlated with failure load was Tb.vBMD (Pearson's correlation coefficient, r = 0.66), whereas the correlation with Ct.Th was low (r = 0.35) [14].…”
Section: Discussionmentioning
confidence: 99%
“…al. [ 15 18 ] determined the bone volume fraction (BV/TV) and other microstructural parameters of bone from bone medical images using a mapping algorithm. The bone volume fraction (BV/TV) map [ 17 ], which is a measure of bone material density distribution, obtained from a CT image of the proximal portion of a femur is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%